Estimativa do tamanho da primeira maturação sexual da rã - touro, Rana catesbeiana, no sistema Anfigranja de criação intensiva - Lima, Samuel Lopes; Costa, Cristina Lúcia Sant'ana; Agostinho, Cláudio Ângelo [UNESP]; Andrade, Dálcio Ricardo; Pereira Filho, Hélio P. (My University, 1998)
The objective of this research was to study the basic aspects of bullfrog reproduction in Anfigranja system from June 1989 to July 1990. For the 1493 animals involved in this experiment (657 males and 836 females) biometrical data were obtained (weight, length and tympanum diameter) and developmental stages of gonads were determined. Female sizes at first maturation were 10,33 cm and 109,78 g and for males it was around 8,09 cm; all males above 45 g were already in the maturation process. The relationship between tympanum diameter and body length (RTC) was considered a good index for male maturation.
Estimate of bullfrog size at first sexual maturation, Rana catesbeiana, in the intensive growing Anfigranja system
Keywords: Bullfrog reproduction in captivity; Size at first maturation